OPTIMALISASI PEMANFAATAN BUAH TJAMPOLAY DALAM PEMBUATAN CAKE SEBAGAI ALTERNATIF PENGEMBANGAN BUAH LOKAL YANG BERGIZI TINGGI - Tia Listiaty; Chondro Suryono (JURNAL PARIWISATA VOKASI, 2022)
This study aims to 1) Knowing the right formula in making tjampolay cake, 2) Knowing the right processing technique in making tjampolay cake, 3) Knowing consumer acceptance in making tjampolay cake. The research on "Utilization of tjampolay fruit in cake making as an alternative ingredient for local development" was conducted at the writer's house in Talun sub-district, Cirebon city. A research study entitled "Utilization of tjampolay fruit in cake making as an alternative material for local development" in the city of Cirebon In the research and development procedure using the ADDIE model developed by Dick and Carry (1996) combined with the 4D model developed by Tiagarajan (1974) so ​​that produce Analysis (study of reference products), Design (product design), Develop (manufacture and testing of products) and Dissemination (exhibition of products). Cake is a cake made from liquid dough by mixing four basic ingredients, namely flour, sugar, eggs and fat, then molded in a pan and baked in the oven until cooked. Tjampolay fruit is a typical fruit from the city of Cirebon with a distinctive taste, namely sweet and fragrant aroma. In addition, this fruit also knows no season, meaning that it bears fruit throughout the season. The fruit contains calories, starch, vitamins, minerals and fiber. The tjampolay fruit is a soft yellow color similar to a sweet potato. In this study, the use of tjampolay fruit as the basic ingredient or filling of the cake was carried out. The method used is to determine the solution and the output targets as well as the steps for each solution given, as well as the method that will be used in achieving these goals. The results showed that 1) the right recipe for making Tjampolay Cake products was using 100% Tjampolay Fruit as a substitute for Banana Fruit. 2) Public acceptance of Cake Tjampolay characteristics of color 3.5, aroma 3.5, texture 3.5, taste 3.62, and overall 3.54. 3) It can be seen from the panelist test that the level of acceptance of the color character in Cake Tjampolay products reached 3.0, the aroma in the Cake Tjampolay products reached 3.00, the texture of the Cake Tjampolay products reached 3.3 and the taste of the Cake Tjampolay products reached 3.3. So it can be concluded that Cake Tjampolay products can be well received by the public